Somatoform disorders in the family doctor's practice - Prykhodko V.Yu.; Mikropulo I.R.; Oleinik M.V.; Kononenko E.A.; Moreva D.Yu.; Gogol O.V.; Kashkovskiy D.O.; Lisnyak O.A.; Lisnyak A.I. (Medičnì Perspektivi, 2013)
In the second part of the article devoted to the problem of somatoform disorders, hypochondriacal disorder, somatoform dysfunction of the autonomic nervous system and sustained somatoform pain disorder are reviewed. Vegetative dysfunction can occur as a separate disorder and may be accompanied by a variety of somatic diseases which distorts and exacerbates their symptoms. In patients with arterial hypertension the authors revealed the presence of vegetative dysfunction in 90%, which correlated with an anxiety disorder by the HADS scale. In clinical practice there are permanent and paroxysmal vegetative dysfunctions. The last ones are manifested by vegetative crises with predominance of sympathoadrenal or vagus-insular symptoms. Approaches to treatment of vegatative disorders and drugs of various pharmacological groups are also discussed in the article. Based on the analysis of published data it is shown that non-benzodiazepine anxiolytic drug Adaptol in single or combined therapy in patients with somatoform disorders promotes fast and effective reduction of mental, emotional and vegetative components of the disease, without limiting work performance and activity of patients.